The Effect of Animal Hunting and Rounders Games on Locomotor and Manipulative Motion Capabilities - Febrianto, Faizal Adin; Kartiko, Dwi Cahyo; Sriwahyuni, Endang (International Journal for Educational and Vocational Studies, 2020)
Elementary school-age children are very active so they prefer to play. Before starting the learning activities, the teacher designs a learning model that is interspersed with games so that the child can receive the material well and is not easily bored during the learning process. In other words, the activities carried out by children are more directed to the activities of playing and moving. One game that is loved and often played by children is hunting animals and baseball. The purpose of this study is to analyze: (1) studying and analyzing the effect of the application of animal hunting game learning models on locomotor and manipulative motion abilities. (2) to study and analyze the effect of the application of baseball game learning models to increase locomotor and manipulative motion skills. (3) to find out, study and analyze the effect of learning based on game hunting animals and baseball to increase locomotor and manipulative mobility. This type of research used in this study is quantitative with a research design using a two-group pre-test post-test design, with data analysis using paired sample t-test and independent sample t-test. The results showed: (1) there was an effect of the application of animal hunting games to locomotor and manipulative mobility. (2) there is an effect of the application of baseball games on locomotor and manipulative motion abilities. (3) in an animal hunting game, the locomotor base motion has an increase of 2.17 and manipulative motion has an increase of 5.1. In a baseball game, the locomotor base motion has an increase of 1.5 and manipulative base motion has an increase of 3.77. Based on the above analysis, it can be concluded that there is an increase in locomotor and manipulative movement abilities for each group after being given a game. Also, there are differences in influence between the animal hunting group and the baseball group as seen from the increase in locomotor motion through independent sample t-test where the game of animal hunting gives a better effect than the game of baseball.